Risk assessment for influenza D in Europe. Issue 6 (4th June 2020) - Chiapponi, Chiara; Ducatez, Mariette; Faccini, Silvia; Foni, Emmanuela; Gaudino, Maria; Hägglund, Sara; Luppi, Andrea; Meyer, Gilles; Moreno, Ana; Näslund, Katarina; Nemanichvili, Nika; Oliva, Justine; et al.
Abstract : Recent studies have identified a new genus of the Orthomyxoviridae family, Influenza D virus (IDV). This virus was shown to infect farm animals including swine and cattle, and to efficiently replicate and transmit in ferrets, the animal model of choice for transmission of influenza A virus to humans. This partnering grant on IDV addressed the need for capacity building at EU level to improve the EU's scientific assessment capacity and international competitiveness. We have promoted cross‐disciplinary cooperation between the partner institutes representing six Member States (BE, FR, IT, LU, NL and SE). We have shown that the available antigen and genome test systems allow reliable influenza D diagnostics in partners laboratories, while for a few of the applied antibody testing methods adjustments are recommended. Tools were developed to study virus‐host range, with a gain of knowledge on host and tissue tropism of IDV in farm animals but also in wild life and very preliminary data was generated on human tissues. Serological results in European cattle suggest that influenza D virus is enzootic. Virus diversity is still unfolding: new virus introductions were identified, as well as new reassortants whose differential clinical impact or cross‐protection levels are still poorly understood. Considering drivers of emergence, IDV was in the top five in comparison with 29 other diseases. The main risk factors of IDV in cattle are related to the animal density, presence of respiratory clinical signs in cattle and contact rates between animals. Simplified quantitative IDV risk assessment exposure model indicated a possible infection of human by IDV through aerosols in cattle farms. Further studies are warranted to fully assess the risk of IDV for both animal and Human health in Europe.